Heavy metals concentrations and speciation of Pb and Ni in airborne particulate matter over two residential sites in Greater Cairo – reflection from synchrotron radiation. (22nd April 2022) - Monged, Mohamed H. E.; Imam, N. G.; Aquilanti, Giuliana; Pollastri, Simone; Rashad, A. M.; Osán, János
Abstract : XANES and X‐ray fluorescence combined with inductively coupled plasma‐mass spectrometry were used to quantify and identify heavy metals concentrations as well as the chemical speciation of Pb and Ni, which have considerable public health impacts in Egypt. Abstract : Synchrotron radiation‐based techniques [X‐ray absorption near‐edge structure (XANES) and X‐ray fluorescence (XRF)] combined with inductively coupled plasma‐mass spectrometry (ICP‐MS) were used for the assessment of heavy metals concentrations as well as lead (Pb) and nickel (Ni) speciation in airborne particulate matter (PM10 ) over two residential sites in Greater Cairo. Nineteen 24 h high‐volume samples collected at Giza (G) Square and Helwan (H) University (Egypt) were selected for this study. Mean concentrations of heavy metals in PM10 at both sites were found to have the same descending order of Pb > Cu > Ni > Cd > Co > As, of which concentrations of Pb, Cu, Ni and Cd in H samples were higher than those in G samples. For Pb, synchrotron‐based XRF results were in good agreement with concentrations obtained by ICP‐MS. The XANES spectra of PM10 at the Pb L 2 ‐edge and Ni K ‐edge were compared with those of Pb and Ni in model standard compounds to provide information on the potential oxidation states as well as the chemical forms of those elements. The data show that Pb has similar chemical environments in both series G and H with the predominance of Pb 2+ oxidation state. Nickel was found as Ni(OH)2, NiO and Ni metal in the analyzed samples. However, the content of Ni in the background filter shows a very strong interference with that of the collected PM10 . Carcinogenic and non‐carcinogenic risks resulting from the inhalation of the studied heavy metals were assessed for children and adult residents and were found below the safe limits, at both sites.